AMBIGU PENDIDIKAN DERADIKALISASI BAGI TERPIDANA TERORISME - Patrisia Mutia Jersi Hartiana (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2021)
Deradicalization is a war of mind against radicalism, therefore theological dialogue is the core. Deradicalization of education is a planned, integrated, systematic, andcontinuous process that is carried out to eliminate or reduce and restore the radical understanding of terrorism that has occurred. Furthermore, it needs to be reinforced by other programs such as psychological, intellectual, and skill development. Families as the community involvement is needed to support convicted terrorists to socialize and well integrated toward general public. Nevertheless, the currently problem is deradicalization education for convicted terrorists cases still focuses on rights rather than obligations. Thus, the arrangements of deradicalization education are needed to be included as an obligation for convicted terrorists. as well as for those convicted of terrorism. It needsto conduct the deradicalizationeducationatthosepenitentiary. Essentially, the government and legal drafters should make provisions of obligation as the formulation stage for convicted terrorism. The correctional institutions are expected to provide deradicalization education.Convicts, Terrorism